Calibration method affects the measured δ2H and δ18O in soil water by direct H2Oliquid–H2Ovapour equilibration with laser spectroscopy. Issue 2 (20th November 2019) - Wang, Hongxiu; Si, Bingcheng; Pratt, Dyan; Li, Han; Ma, Xiaojun
Abstract: The direct H2 Oliquid –H2 Ovapour equilibration method utilizing laser spectroscopy (DVE‐LS) is a way to measure soil pore water stable isotopes. Various equilibration times and calibration methods have been used in DVE‐LS. Yet little is known about their effects on the accuracy of the obtained isotope values. The objective of this study was to evaluate how equilibration time and calibration methods affect the accuracy of DVE‐LS. We did both spiking and field soil experiments. For the spiking experiment, we applied DVE‐LS to four soils of different textures, each of which was subjected to five water contents and six equilibration times. For the field soil experiment, we applied three calibration methods for DVE‐LS to two field soil profiles, and the results were compared with cryogenic vacuum distillation (CVD)‐LS. Results showed that DVE‐LS demonstrated higher δ 2 H and δ 18 O as equilibration time increased, but 12 to 24 hr could be used as optimal equilibration time. For field soil samples, DVE‐LS with liquid waters as standards led to significantly higher δ 2 H and δ 18 O than CVD‐LS, with root mean square error (RMSE) of 8.06‰ for δ 2 H and 0.98‰ for δ 18 O. Calibration with soil texture reduced RMSE to 3.53‰ and 0.72‰ for δ 2 H and δ 18 O, respectively. Further, calibration with both soil texture and water content decreased RMSE to 3.10‰ for δ 2 H and 0.73‰ for δ 18 O. Our findings conclude that the calibration method applied may affect the measured soil water isotope values from DVE‐LS.